Holomorphology and systematics of the eastern Nearctic stonefly genus Remenus Ricker (Plecoptera: Perlodidae) - Verdone, Chris J., author; Kondratieff, Boris, advisor; Ode, Paul, committee member; Clements, William, committee member (Colorado State University. Libraries, 2018)
The holomorphology of the eastern Nearctic stonefly genus Remenus Ricker is reviewed using scanning electron microscopy, color photomicrographs and COI DNA barcodes. Examination of all life stages has resulted in new comparative descriptions and a new key to adults. Remenus daniellae Verdone and Kondratieff, sp. n. is described from Great Smoky Mountains National Park, North Carolina and Tennessee, U.S.A. The new species is the fourth species to be included in the genus Remenus and is differentiated from R. bilobatus (Needham and Claassen, 1925), R. duffieldi Nelson and Kondratieff, 1995, and R. kirchneri Kondratieff and Nelson, 1995 by the short clavate epiproct with palmate hair-like spinulae. Nymphs can tentatively be separated into two groups based on basal cercal setal length: (1) variable length setae, R. bilobatus and R. daniellae sp. n., and (2) short setae, R. duffieldi and R. kirchneri. With the application of known distributions, nymphs of R. kirchneri and R. duffieldi may be distinguished from R. bilobatus and R. daniellae sp. n. However, sympatry and range overlap precludes the use of this character in distinguishing R. bilobatus and R. daniellae sp. n. Ova of the four species apparently lack distinguishing characteristics and thus are not separable at this time. Distribution maps, biological notes, and a neighbor-joining tree based on COI DNA barcodes are also presented. Three species, R. daniellae sp. n., R. duffieldi and R. kirchneri are apparently restricted to the Blue Ridge Physiographic Province in the southern Appalachian Mountains. Based on Nature Serve global conservation rankings these species are of high conservation concern. Maximum entropy modeling was used to identify potentially suitable habitats for these species. Model results were used to identify differences in the bioclimatic envelope inhabited by each species, and assess the current status of habitat protection. The models were able to successfully predict the potential distributions of R. daniellae sp. n., R. duffieldi and R. kirchneri. Model evaluation metrics were generally good, AUC = 0.83–0.90, and spatial predictions were plausible. Model results for R. kirchneri differed from both R. daniellae sp. n. and R. duffieldi in both environmental variable selection and percent contribution of these variables. Model response curves for R. daniellae sp. n. and R. duffieldi exhibited similar responses to environmental variables, which is not surprising as these species occupy similar habitats in relatively close geographic proximity. The amount of protected habitat varied between species. Based on model results, R. kirchneri had the least potentially suitable habitat in protected areas. Additional field surveys are needed to provide new occurrence records that can be used to create more accurate and refined distribution models.
Keywords: Maxent; systematics; new species; Remenus; Plecoptera; Appalachians